2007
DOI: 10.1016/j.ejphar.2007.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Reinstatement of cocaine place-conditioning prevented by the peptide kappa-opioid receptor antagonist arodyn

Abstract: Stress contributes to the reinstatement of cocaine-seeking behavior in abstinent subjects. Kappaopioid receptor antagonists attenuate the behavioral effects of stress, potentially providing therapeutic value in treating cocaine abuse. Presently, the peptide arodyn produced long-lasting kappa-opioid receptor antagonism, suppressing kappa-opioid receptor agonist-induced antinociception at least 3 days after intracerebroventricular administration of 0.3 nmol. C57Bl/6J mice demonstrated cocaine-conditioned place p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
156
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(171 citation statements)
references
References 28 publications
15
156
0
Order By: Relevance
“…The findings of the present study are consistent with previous reports (Beardsley et al 2005;Carey et al 2007;Valdez et al 2007). Beardsley et al (2005) showed that intermittent and uncontrollable footshock was able to reinstate active lever responding on a lever previously associated with cocaine self-administration and that pre-treatment with the kappa antagonist JDTic attenuated footshock-induced cocaine-seeking behavior.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The findings of the present study are consistent with previous reports (Beardsley et al 2005;Carey et al 2007;Valdez et al 2007). Beardsley et al (2005) showed that intermittent and uncontrollable footshock was able to reinstate active lever responding on a lever previously associated with cocaine self-administration and that pre-treatment with the kappa antagonist JDTic attenuated footshock-induced cocaine-seeking behavior.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, both the footshock and forced swim were administered in a different apparatus and room in the reinstatement protocol described in the present study. This is consistent with recent reports from other research groups also showing that stress exposure outside the experimental chamber was able to reinstate drug seeking (Carey et al 2007;Kreibich andBlendy 2004, Ribeiro Do Cotuo et al 2006). Differences between reinstatement results obtained using operant self-administration protocols and place-conditioning protocols likely reflect the differences in the underlying learning mechanisms.…”
Section: Clinical Implications Of Kappa Antagonism On Drug Reinstatementsupporting
confidence: 92%
See 3 more Smart Citations